Pengaruh Religiusitas dan Keterampilan Sosial Terhadap Kecemasan Bertanding - Hendra Iskandar; Muhammad Ismail Ismail; Moh. Usbah; Moh. Adhan (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Based on the results of the author's brief observation at the Tadulako Pencak Silat College, Central Banawa District, Donggala Regency, it was found that the competition anxiety of athletes was still less than ideal. Two factors that were thought to have an effect on the level of competition anxiety of athletes were religiosity and social skills. The aims of this study were: 1) To find out whether there was an effect of religiosity on the competition anxiety of athletes at the Tadulako pencak silat college, Central Banawa District, Donggala Regency; 2) To find out whether there was an effect of social skills on the competition anxiety of athletes at the Tadulako pencak silat college, Banawa Tengah District, Donggala Regency. This study used ex-post facto research design. The instrument to measure the three variables in this study was a closed questionnaire. The population in this study were all athletes from the Tadulako Pencak Silat College, Central Banawa District, Donggala Regency, totaling 28 athletes. The sampling technique used a saturated sampling technique, so that the number of samples was the same as the total population of 28 athletes. The data analysis technique using SPSS application. The results showed: 1) There was no effect of religiosity on the competition anxiety of athletes at the Tadulako pencak Silat College, Central Banawa District, Donggala Regency; 2) There was an effect of social skills on the competition anxiety of athletes at the Tadulako pencak silat college, Central Banawa District, Donggala Regency. As an implication, the results of this study can be used as input for coaches in doing talent scouting and making mental training programs for athletes.